THE ROLE AND PLACE OF HUMORAL IMMUNITY IN BONE REGENERATION - Napasov, I.Z.; Hamdamov, B.Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The immune system is actively involved in bone regeneration. This reasoning may stem from the peculiarities of immune cell populations, which are known to be diverse and heterogeneous. Such functional and cytological versatility of bone tissue, to a certain extent, may indicate the similarity of their natural relationship. The basis of this connection is regenerative processes, which we decided to describe in this review article.